Hard facts, dangerous half-truths, and total nonsense : profiting from evidence-based management - Pfeffer, Jeffrey; Sutton, Robert I. (Boston, Mass. : Harvard Business School Press, 2006)
"Through evidence-based management, business leaders face the hard facts and act on the best evidence - trumping the competition. They also view common beliefs about effective management with healthy skepticism. To demonstrate the dangers lurking in such beliefs, the authors dismantle six widely held - but ultimately flawed - half-truths in core management areas including leadership, strategy, change, talent, incentives, and the connections between work and the rest of life. Pfeffer and Sutton describe how to identify and apply practices that are best for their companies, rather than blindly embrace what seems to have worked elsewhere."--BOOK JACKET.
Why every company needs evidence-based management -- How to practice evidence-based management -- Is work fundamentally different from the rest of life and should it be? -- Do the best organizations have the best people? -- Do financial incentives drive company performers? -- Strategy is destiny? -- Change or die? -- Are great leaders in control of their companies? -- Profiting from evidence-based management.
Includes bibliographical references (pages [239]-260) and index.
Description based on print version record.
Keywords: Industrial management -- Decision making; Gestion d'entreprise -- Prise de décision; Prise de décision; Gestion d'entreprise.; Management; Industrial management -- Decision making; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books